Simulation Nongravitational Dynamic of Cometary Orbit - Arsini, Arsini; Saefan, Joko; Farchani Rosyid, Muhammad (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2015)
The tail formation of a comet near the sun leads to the situation in which the comet continually losses a part of its masses so that the mass of the comet decreases monotonically. A comet may also accrete the material encountered along its orbit so that its mass increases. Therefore, the mass of a comet can be regarded as a function of time. In this work we study simulation the dynamics of the orbit of a comet due to the lost of its mass along the formation of its tail and the material accretion along its orbit. Here, we assume that the comet under consideration is of the form of a ball and rotates so rapidly that the whole of its surface catches the radiation of the sun equally.